Upaya Meningkatkan Motivasi Dan Hasil Belajar Siswa pada Materi Menentukan Ide Pokok Paragraf dengan Teknik Membaca Intensif di SD Negeri Bambalo - Asmin A Kandupi (Universitas Pendidikan Mandalika, 2021)
This study aims to improve student motivation and learning outcomes in determining the main idea of paragraphs using intensive reading techniques at SD Negeri Bambalo. This research method uses classroom action research conducted in 2 cycles. The research subjects were 9 grade students of SDN Bambalo Semester 1 in the academic year 2020/2021. Data collection techniques in this study used tests and documentation. The data validation used triangulation techniques. The results of this study indicate that the application of an intensive reading technique approach to the material of determining the main idea of paragraphs can increase student motivation and learning outcomes. The class average score increased from 56.99 in the initial study, to 72.88 in the first cycle, and in the second cycle to 81.88 with the level of completeness of learning from 2 students or 22.22% in the initial conditions to 5 students or 55.55% in the first cycle and 8 students or 88.89% in the second cycle. The increase in learning motivation is also getting better, in the initial study there were 2 students or 22.22% of 9 students, in cycle I, students were complete as seen from the learning motivation of 5 students or 55.55% of 9 students, and in cycle II, Incomplete seen from the learning motivation of 9 students or 100% of 9 students. The conclusion is that the application of intensive reading techniques can increase motivation and learning outcomes of fifth grade students of SDN Bambalo Semester 1 in the 2020/2021 academic year.